Protease-activated receptors (PAR)-1 and -3 drive epithelial-mesenchymal transition of alveolar epithelial cells – potential role in lung fibrosis - Wygrecka, Malgorzata; Didiasova, Miroslava; Berscheid, Sebastian; Piskulak, Katarzyna; Taborski, Brigitte; Zakrzewicz, Dariusz; Kwapiszewska, Grazyna; Preissner, Klaus T.; Markart, Philipp (Thrombosis and Haemostasis, 2013)
Extravascular activation of the coagulation cascade in the lung is commonly observed in pulmonary fibrosis. Coagulation proteases may exert profibrotic cellular effects via protease-activated receptors (PARs)-1 and -2. Here, we investigated the potential role of two other members of the PAR family, namely PAR-3 and PAR-4, in the pathobiology of lung fibrosis. Elevated expression of PAR-3, but not PAR-4, was detected in the lungs of idiopathic pulmonary fibrosis (IPF) patients and in bleomycin-induced lung fibrosis in mice. Increased PAR-3 expression in fibrotic lungs was mainly attributable to alveolar type II (ATII) cells. Stimulation of primary mouse ATII, MLE15 and A549 cells with thrombin (FIIa) – that may activate PAR-1, PAR-3 and PAR-4 – induced epithelial-mesenchymal transition (EMT), a process that has been suggested to be a possible mechanism underlying the expanded (myo)fibroblast pool in lung fibrosis. EMT was evidenced by morphological alterations, expression changes of epithelial and mesenchymal phenotype markers, and functional changes. Single knockdown of FIIa receptors, PAR-1, PAR-3, or PAR-4, had no major impact on FIIa-induced EMT. Simultaneous depletion of PAR-1 and PAR-3, however, almost completely inhibited this process, whereas only a partial effect on FIIa-mediated EMT was observed when PAR-1 and PAR-4, or PAR-3 and PAR-4 were knocked down. PAR-1 and PAR-3 co-localise within ATII cells with both being predominantely plasma membrane associated. In conclusion, our study indicates that PARs synergise to mediate FIIa-induced EMT and provides first evidence that PAR-3 via its ability to potentiate FIIa-triggered EMT could potentially contribute to the pathogenesis of pulmonary fibrosis.
Keywords: Coagulation proteases; thrombin; protease-activated receptors; pulmonary fibrosis; epithelial-mesenchymal transition